The compliance game: Legal endogeneity in anti-bribery settlement negotiations - Hock, Branislav (International journal of law, crime and justice, 2022)
In line with a wider expansion of global governance tools to prevent and punish corruption, the enforcement of anti-foreign bribery laws is increasing. Yet few cases are tested in court; rather, confidential negotiations and out-of-court settlements have become the norm. Many argue that this favours the enforcement authorities, since even firms with a good defence are reluctant to risk a trial when settlement appears a safer option, but there is very little evidence about what really happens in anti-foreign bribery negotiations and how companies and enforcement authorities interact during this process. Through qualitative research with participants in negotiations for settlements of the United States Foreign Corrupt Practices Act and the United Kingdom Bribery Act, we find evidence that companies have considerable power to influence how the law is interpreted and implemented. In particular, companies use compliance programs to signal good character, while enforcement authorities willingly accept these symbols as justification for settling out of court or acting leniently. Companies therefore play a key role in shaping the law in places where it is ambiguous, an interesting example of ‘legal endogeneity’, whereby the subjects of the law help to shape its meaning.